Non-genetic factors affecting first lactation reproduction traits of frieswal heifers/ cows under field conditions (Indian Journal of Animal Production and Management, 2017)
Frieswal (HF x Sahiwal) are the important crossbred cattle population in India for milk production. An  investigation was carried out with farmers of U.S. Nagar district of Uttarakhand on Frieswal heifers/ cows  during Nov. 2010 to Feb. 2016 to study the effect of various non-genetic factors (blocks, herd size, land  holding, education level of farmers, caretakers of herd, marketable milk surplus, season/ year of birth/  calving) on age at first service, age at first conception, no. of services required for first conception, age at  first calving, first service period and first calving interval using least-squares analysis of variance. The overall  least-squares means for these traits were 840.7±57.9 days, 906.6±64.9 days, 1.75±0.29, 1103.2±80.6 days,  142.1±4.2 days and 520.1±47.4 days based on 569, 539, 538, 337, 163 and 88 observations, respectively.  These traits were significantly affected by varying non-genetic factors. Information on this aspect is useful  in implementing any large scale field based animal breeding program with respect to crossbred cattle in  general and Frieswal cattle in particular.
Keywords: First lactation; Frieswal cattle; Reproduction traits